Efficacy of Diatomaceous Earth and Vitellariaparadoxa Seed Oil in Storage of Cowpea under Ventilated and Non-ventilated Conditions (2019)
Sto.age of cowpea is highly constrained by insect pest infestation and losses caused by the cowpea weevil (Callosobruchus maculatus, F.) are high. Several methods have been used over the years to protect cowpea grains in storage, but the use of synthetic insecticides is very dominant and this has led to problems, such as the killing of non-target species, user hazards, harmful food residues, and evolution of resistance to chemicals. A search for alternative insect pest control methods which are relatively less harmful to the user and cheaper has become essential. The effectiveness of Diatomaceous earth (DE) and Vitellaria paradoxa seed oil (VPSO) for cowpea storage in polypropylene and jute bags under ventilated and non-ventilated storeroom conditions were investigated over three months period. Crude DE was applied at a dose rate of 1 g/kg of cowpea and a diluted concentration (10% v/v) of VPSO of 400 mL was mixed with 8 kg of cowpea. Live insect count, dead insect count, and germination percentage were assessed weekly while proximate analysis was carried out before and after storage. Mean live insect count increased in the ventilated store-room from 0.67±0.34 to 36.13±19.51insects/kg after 1 month and 3 months of storage respectively for untreated cowpea. Insect population in treated samples increased from 0.38±0.26to 24.78±23.33, and from 0.17±0.30 to 10.75±5.27 for DE and VPSO treated samples, respectively. In the non-ventilated storeroom, insect population increased from 0.33±0.26 to 36.96±19.09 for untreated cowpea, 0.17±0.20 to 33.08±30.07 for DE and 0.21±5.63 to 8.17±11.30 for VPSO treated cowpea. Based on insect count, both treatments were very effective in controlling cowpea weevil in the first two months of storage, however their potency reduced by the third month. The potency of DE deteriorated faster compared to VPSO however, DE treated cowpea was most effective , or retaining seed germination in both ventilated and non-ventilated storerooms. Proximate analysis showed that cowpea treated with both treatments had similar nutrient composition after storage. Diatomaceous earth and Vitellaria paradoxa seed oil have potentials in their raw form for short term insect pest control in the storage of cowpea.